Active recovery strategy and lactate clearance in elite swimmers - Faghy, M. A.; Lomax, M.; Brown, P. I. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Swimming requires sustained high performance, with limited recovery between heats, recovery strategies are essential to performance but are often self-regulated and sub-optimal. Accordingly, we investigated a physiologically determined recovery protocol. METHODS: Fifteen (m=9, f=6) international junior age group swimmers participated in this study. The average age of the participants was 15.8±1.5 years. All participants completed a lactate elevation protocol (8 x 50 m sprints), followed by one of three recovery strategies: 1) velocity at lactate threshold (VLT); 2) coach prescribed protocol (COA); and 3) national governing body recommendations (NGB) and thereafter a 200-m time trial. RESULTS: [lac-]B was similar between trials at baseline (pooled data: 1.3±0.4 mmol/l-1, P>0.05) but increased following 8x50 m sprints (pooled data 9.5±3.5 mmol/l-1, P<0.05) and reduced in all conditions (mean reduction 6.4±1.7 mmol/l-1). [lac-]B remained elevated following NGB (5.6±0.8 mmol/l-1, P<0.05) compared with COA (2.3±1.7 mmol/l-1) and VLT (1.7±1.2 mmol/l) but was blunted during the 200-m time trial in VLT (6.4±1.7 mmol/l-1, P<0.05). Time trial performance was similar between trials; VLT (2.24±0.12 min), COA (2.23±0.14 min) and NGB (2.22±0.13 min, P>0.05). CONCLUSIONS: Despite similar performance, individually prescribed recovery strategy with a physiological basis will preserve repeated exercise performance performed on the same day.